The Evolution and Efficiency of the Insurance Sector in the Republic of Moldova in the Context of Ensuring Citizens’ Security and Well-Being - Mulic, Andrei; Labliuc, Sveatoslav (Acta Universitatis Danubius. Œconomica, 2025)
Objectives: This paper examines the evolution and efficiency of the insurance sector in the Republic of Moldova, with a focus on its contribution to strengthening citizens’ economic security and overall well-being. Prior Work: The study builds on existing literature on insurance markets in emerging economies and complements the authors’ previous research regarding the role of innovation and digitalization in increasing access to financial protection. The research is conducted within the project “Strengthening socio-economic and legal mechanisms to ensure the well-being and security of the citizens” (COUNCIL 01.05.02). Approach: The analysis is based on economic and financial indicators of the Moldovan insurance market during the period 2018–2023, supplemented by data on insurance penetration rate, gross premiums written, claims ratio, and the level of digitalization. Results: The insurance sector in the Republic of Moldova shows modest but consistent growth, with significant potential for development through innovation and well-adapted public policies. Implications: The findings highlight the need for proactive policies to build public trust and improve access to relevant insurance products. Value: The study offers a comprehensive overview of sectoral performance and proposes strategic directions for transforming the industry into a pillar of sustainable financial security.